Mother to Child Transmission of Extended Spectrum β-Lactamase Producing Enterobacteriaceae. (4th October 2017) - Danino, Dana; Melamed, Rimma; Sterer, Batya; Porat, Nurith; Gushanski, Alex; Shany, Eilon; Greenberg, David; Borer, Abraham
Abstract: Background: Preterm infants are at high risk for extended spectrum β-lactamase producing Enterobacteriaceae (ESBL-E) sepsis and neonatal intensive care unit (NICU) outbreaks. There is no consensus regarding surveillance of pregnant women for ESBL-E colonization. However, neonatal screening is accepted in order to prevent NICU's transmissions by contact isolation. We hypothesized that a significant proportion of ESBL-E colonized infants in our NICU were due to mother-to-child transmission. The aim of this study was to molecularly identify pairs of mothers and offspring ESBL-E colonization. Methods: The Soroka University Medical Center serves the entire population of southern Israel with an estimated 17, 000 deliveries per year. This was a one year analysis from an ongoing, prospective, active rectal ESBL-E colonization surveillance of mothers of premature infants and their offspring. Pairs of mothers and infants colonized with the same bacteria underwent molecular identification by pulse-field gel electrophoresis (PFGE). Results: Between January 2015 and February 2016, 311(76%) out of 407 mothers and all 477(100%) infants were screened for ESBL-E colonization; carriage rates were 21.5% and 14.9%, respectively. Four (5.6%) carrier infants developed late onset sepsis and 2 (2.8%) died. Mothers of 47% (28) ESBL-E carrier infants were colonized at delivery; comparison of the characteristics between colonized infants of positively and negatively screened mothers is presented in Table 1. Twenty-three (34.3%) colonized mothers delivered 25 infants who were found to be colonized with the same bacterial strain according to species' identification and antibiogram. A subgroup of 10 mother-infant dyads underwent PFGE and 70% shared identical molecular fingerprint patterns. No similarities were found between isolates recovered from unrelated neonates and mothers. Conclusion: High ESBL-E carriage rates in mothers and NICU'S infants, in our region, with a non-negligible maternal-neonatal ESBL-E colonization transmission illuminates the importance of maternal ESBL colonization surveillance and further consideration regarding infectious control preventive measurements. Disclosures: All authors: No reported disclosures.